HEALTH AND NUTRITIONAL STATUS OF CHILDREN UNDER FIVE YEARS IN POSYANDU NUTRITION PROGRAM - Dadang Sukandar; Ali Khomsan; Faisal Anwar; Hadi Riyadi; Eddy Setyo Mudjajanto (Food and Nutrition Society of Indonesia, 2010)
The objectives of this research were to analyze health, nutritional status of children under five years and its influential factors. This research was carried out in two sub-districts of Bogor: Sub-District of Ciomas and Sub-District of Darmaga. As many as 16 posyandu nutrition program were obtained. A total number of 240 mothers had been divided into control and intervention groups. Baseline data were collected during the pre-study, while endline data were collected after conducting intervention (experiment). The experiment had been conducted for five months in the form of providing nutrition education once in two weeks and implementing home gardening. The data analysis included estimation of mean, standard deviation, minimum value, maximum value and proportion. Based on the General Linear Model (GLM) analysis, it was found that intervention had significant impact on the nutritional status (WAZ) of children under five years. Intervention did not have significant effects on the nutritional status according to HAZ and WHZ. Key words: .